2020
DOI: 10.5194/egusphere-egu2020-4053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study of the distribution of Rare Earth Elements in soil and in Vitis Vinifera L.cv Cannonau in two different regions

Abstract: <p>Vitis vinifera L. cultivar “Cannonau” (Magnoliopsida Vitaceae) has been grown for years in the Italian regions to produce a fine wine, with Controlled Designation of Origin (DOC) and Denomination of Controlled and Guaranteed Origin, (DOCG). The International Organization of Vine and Wine (OIV) defined the “terroir” as “a concept which refers to a specific area in which the interactions between the physical and biological env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study of the environmental geochemistry of REEs in viticulture in a general sense, and in vineyard soils in particular, has attracted increasing attention in the last two decades (Mihucz et al, 2006;Rossano et al, 2007;Bertoldi et al, 2009Bertoldi et al, , 2011Censi et al, 2014;Pisciotta et al, 2017;Pepi et al, 2016a, b;Punturo et al, 2018;Pepi et al, 2020). These studies have shown that vineyard soils can contain high concentrations of both heavy metals and REEs and this finding has encouraged studies aimed at identifying the contents of such elements and their influence on wine quality.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the environmental geochemistry of REEs in viticulture in a general sense, and in vineyard soils in particular, has attracted increasing attention in the last two decades (Mihucz et al, 2006;Rossano et al, 2007;Bertoldi et al, 2009Bertoldi et al, , 2011Censi et al, 2014;Pisciotta et al, 2017;Pepi et al, 2016a, b;Punturo et al, 2018;Pepi et al, 2020). These studies have shown that vineyard soils can contain high concentrations of both heavy metals and REEs and this finding has encouraged studies aimed at identifying the contents of such elements and their influence on wine quality.…”
Section: Introductionmentioning
confidence: 99%